2015
DOI: 10.5812/aapm.5(3)2015.25032
|View full text |Cite
|
Sign up to set email alerts
|

Oral Dexmedetomidine Versus Midazolam as Anesthetic Premedication in Children Undergoing Congenital Heart Surgery

Abstract: Background:Premedication is required for reducing anxiety and child’s struggling against mask acceptance on anesthesia in pediatric surgery for congenital heart disease. Midazolam has been widely used for this purpose, but because of its side effects, finding an effective replacement with less complication is necessary.Objectives:In the present study, we compared the efficacy of oral midazolam versus dexmedetomidine in terms of anxiolysis and mask acceptance behavior.Patients and Methods:Sixty children aged be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 13 publications
0
26
1
Order By: Relevance
“…Our study is consistent with the conclusions of the study by Jun et al e RSSs in the two groups showed sedation scores of 2 to 3, and satisfactory results were achieved in terms of separation from parents and mask acceptance. Faritus et al found that children that received preoperative oral administration of 0.5 mg/kg midazolam or 2 μg/kg dexmedetomidine can be easily separated from their parents and received an anesthesia mask without significant hemodynamic changes during congenital heart disease surgery [20]. Similarly, no significant difference in changes in blood pressure and HR were found between the two groups in our study.…”
Section: Discussioncontrasting
confidence: 47%
“…Our study is consistent with the conclusions of the study by Jun et al e RSSs in the two groups showed sedation scores of 2 to 3, and satisfactory results were achieved in terms of separation from parents and mask acceptance. Faritus et al found that children that received preoperative oral administration of 0.5 mg/kg midazolam or 2 μg/kg dexmedetomidine can be easily separated from their parents and received an anesthesia mask without significant hemodynamic changes during congenital heart disease surgery [20]. Similarly, no significant difference in changes in blood pressure and HR were found between the two groups in our study.…”
Section: Discussioncontrasting
confidence: 47%
“…Dexmedetomidine is regarded as an effective drug to prevent PD attack due to its functions of antianxiety, improvement of sleep quality, and analgesia. [27][28][29] All enrolled patients in this study received routine dexmedetomidine infusion during surgery; meanwhile, dexmedetomidine was prohibited after surgery except for delirium occurrence. Therefore, all participants in this study had the same baseline for dexmedetomidine administration.…”
Section: Discussionmentioning
confidence: 99%
“…Four RCTs (Ghali et al, 2011;Liu et al, 2014;Faritus et al, 2015;Kumari et al, 2017) compared midazolam oral solution with dexmedetomidine, including 300 children. Two RCTs demonstrated no significant difference [MD = −0.07 to 0.08, P > 0.05].…”
Section: Depth Of Sedationmentioning
confidence: 99%
“…A total 33 studies were included, including 20 RCTs, three cohort studies, nine case series, and one case report. The results of RCTs (Weldon et al, 1992;Mitchell et al, 1997;D'agostino and Terndrup, 2000;Luhmann et al, 2001;Younge and Kendall, 2001;Debnath and Pande, 2003;Horiuchi et al, 2005;Keidan et al, 2005;Mishra et al, 2005;Yildirim et al, 2006;Ashrafi et al, 2013;Derakhshanfar et al, 2013;Hijazi et al, 2014;Liu et al, 2014;Zhai et al, 2014;Faritus et al, 2015;Khodadad et al, 2016;Li et al, 2017;Salehi et al, 2017;You et al, 2018) and prospective cohort studies (Nathan and Vargas, 2002;Schmalfuss, 2005;Peretz et al, 2014) showed 189 cases of adverse drug reaction (ADR) and that the incidence of ADR was 19.57% (189/966). ADR involved the following: (1) mental system (lethargy, restless sleep, prolonged sedation, euphoria or restlessness, irritability, agitation, abnormal behavior, mood swings, headache, aggressiveness, and inner conflicts); (2) digestive system (nausea, vomiting, and hiccups);…”
Section: Safety Outcomesmentioning
confidence: 99%
See 1 more Smart Citation